Pro DNS and BIND - Aitchison, Ron (Apress, 2012)
Every time you get e-mail, every time you access a web page, you use the Domain Name System (DNS). In fact, over 2 billion such requests hit the DNS root-servers alone every day. Every one of those 2 billion requests originate from a DNS that supports a group of local users, and every one of them is finally answered by a DNS server that may support a high-volume commercial web site or a modest, but much loved, family web site. This book is about understanding, configuring, diagnosing, and securing the DNS servers that do the vital work. HTTP